New recombinant cold-adapted and organic solvent tolerant lipase from psychrophilic Pseudomonas sp. LSK25, isolated from Signy Island Antarctica - Salwoom, Leelatulasi; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Mohd Shariff, Fairolniza; Convey, Peter; Mohamad Ali, Mohd Shukuri (MDPI, 2019)
In recent years, studies on psychrophilic lipases have become an emerging area of research in the field of enzymology. The study described here focuses on the cold-adapted organic solvent tolerant lipase strain Pseudomonas sp. LSK25 isolated from Signy Station, South Orkney Islands, maritime Antarctic. Strain LSK25 lipase was successfully cloned, sequenced, and over-expressed in an Escherichia coli system. Sequence analysis revealed that the lipase gene of Pseudomonas sp. LSK25 consists of 1432 bp, lacks an N-terminal signal peptide and encodes a mature protein consisting of 476 amino acids. The recombinant LSK25 lipase was purified by single-step purification using Ni-Sepharose affinity chromatography and had a molecular mass of approximately 65 kDa. The final recovery and purification fold were 44% and 1.3, respectively. The LSK25 lipase was optimally active at 30 °C and at pH 6. Stable lipolytic activity was reported between temperatures of 5–30 °C and at pH 6–8. A significant enhancement of lipolytic activity was observed in the presence of Ca2+ ions, the organic lipids of rice bran oil and coconut oil, a synthetic C12 ester and a wide range of water immiscible organic solvents. Overall, lipase strain LSK25 is a potentially desirable candidate for biotechnological application, due to its stability at low temperatures, across a range of pH and in organic solvents.